Utilization of Durian Seed Flour as Filler Ingredient of Meatball - D. R. Malini; I. I. Arief; H. Nuraini (Faculty of Animal Science, Bogor Agricultural University, 2016)
Durian seed flour contains starch consisted of amylose and amylopectin like tapioca flour, so it can be utilized as a filler in meatball production. The purposes of this research were to evaluate the nutrient content and quality of durian seed flour, the best level of durian seed flour addition to the meatball production, and the quality of beef meatball during storage in room temperature and refrigerator. Complete randomized design (CRD) was used with 3 treatments and 3 replications. The treatments used different filler ingredients consisted of: 1) 100% tapioca, 2) 50% tapioca + 50% durian seed flour, and 3) 100% durian seed flour utilization. The results showed that durian seed flour could affect the protein levels and hardness of beef meatballs. In the organoleptic test, the addition of durian seed flour had no effect on the appearance of the color, flavor, aroma, and texture. The meatballs with 100% durian seed flour had the lowest hardness. The protein content of the meatballs with 100% durian seed flour was the highest. The used of 50% durian seed flour gave the best effect to beef meatball during storage. Meatball could be stored up to 8 h in room temperature while refrigerator could keep it longer up to 12 d. It was concluded that the addition 50% durian seed flour may substitute tapioca flour as filler ingredient of beef meatball.